INFLUENCE OF NEWSPAPER FRAMING OF COVID-19 VACCINES ON THE PUBLIC PERCEPTION OF THE CONTROVERSIES IN ENUGU STATE, NIGERIA - Christiana Ibenyenwa, Ndidi; Obiageli Osueke, Ngozi; Susan Ogundoyin, Olayinka; Christianah Adedeji, Odunayo (African Journal of Social and Behavioural Sciences, 2024)
This paper aimed to ascertain the influence of newspaper framing of COVID- 19 vaccine controversies on the public perception of these controversies. It was a mixed design of content analysis and cross-sectional survey research methods, anchored on the frameworks of media framing and information processing theories. A multistage sampling technique was employed to select samples. Purposive sampling was used to select two national newspapers for the content analysis study. For the survey, Enugu State was purposively selected and yielded a sample size of 630, 700 from which 384 samples were obtained via Cochran’s sampling formula to obtain a representative sample. The quantitative data generated are presented in tables as frequencies and percentages, and chi-square and logistic regression analyses were employed for the inferential analysis. Chi-square tests were used to test the significant associations between variables, and logistic regression was used to examine the influence of the key independent variable on the dependent variable. At p<=0.05, the null hypothesis could not be rejected as there was no relationship between COVID-19 vaccine controversy framing and perceptions in the study area, among other factors. The study therefore concluded that newspaper framing of COVID-19 vaccine controversies did not influence public perceptions of these controversies.